2020
DOI: 10.3390/md18120631
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptide Arenicin-1 Derivative Ar-1-(C/A) as Complement System Modulator

Abstract: Antimicrobial peptides (AMPs) are not only cytotoxic towards host pathogens or cancer cells but also are able to act as immunomodulators. It was shown that some human and non-human AMPs can interact with complement proteins and thereby modulate complement activity. Thus, AMPs could be considered as the base for complement-targeted therapeutics development. Arenicins from the sea polychaete Arenicola marina, the classical example of peptides with a β-hairpin structure stabilized by a disulfide bond, were shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…In this regard, the family of β-hairpin peptides termed arenicins—isolated from coelomocytes of marine polychaeta Arenicola marina —attracts much attention. There are three members of this family: arenicin-1, -2 containing one disulfide bridge and arenicin-3 with two disulfide bonds [ 3 , 4 , 5 , 6 ]. Natural isoforms of arenicins exhibit a pronounced antimicrobial activity against Gram-negative and Gram-positive bacteria as well as towards yeasts and pathogenic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the family of β-hairpin peptides termed arenicins—isolated from coelomocytes of marine polychaeta Arenicola marina —attracts much attention. There are three members of this family: arenicin-1, -2 containing one disulfide bridge and arenicin-3 with two disulfide bonds [ 3 , 4 , 5 , 6 ]. Natural isoforms of arenicins exhibit a pronounced antimicrobial activity against Gram-negative and Gram-positive bacteria as well as towards yeasts and pathogenic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this study discuss the possibility of interaction of AMPs with complement proteins, C1q and C3, and the regulation of their functional activity [ 158 ]. The influence of structural changes in arenicins on their interaction with complement proteins and biological activity was studied [ 159 ]. The arenicin-1 derivative without a disulfide bond (Ar-1- (C/A)), despite the absence of this bond, retains all important functional activities and also exhibits lower toxicity compared to the natural analogs previously discovered [ 160 , 161 , 162 ].…”
Section: Immunomodulatory Activity Of Ampsmentioning
confidence: 99%
“…Earlier, structure-function relationships of arenicins have been extensively investigated [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Arenicin was shown to modulate the human complement system [ 26 ]. Here, the authors reported the property change in arenicin-1 derivative Ar-1-(C/A) structure and its antimicrobial, hemolytic and complement-modulating activities in comparison with those of the natural peptide.…”
mentioning
confidence: 99%
“…Here, the authors reported the property change in arenicin-1 derivative Ar-1-(C/A) structure and its antimicrobial, hemolytic and complement-modulating activities in comparison with those of the natural peptide. Despite the absence of a disulfide bond, the peptide possessed all important functional features, but its hemolytic activity reduced [ 26 ]. The use of marine peptides as new complement modulators has several advantages.…”
mentioning
confidence: 99%
See 1 more Smart Citation